Analyzing Energy-Saving Measures and Key Metrics for Enhancing Cooling Performance in Atrium Buildings - Saxena, Shashi; Sharma, Anupama (New Approaches in Engineering Research Vol. 8, 2021)
Professional designers and owners are increasingly using atriums to provide a variety of benefits, including ample sunshine, circulation spaces, and surfaces for landscape applications. One of the most serious issues with this popular architectural feature is the space conditioning of atriums, which have a relatively large volume when compared to traditional commercial and institutional spaces. If atriums are fully conditioned, this could result in excessive energy consumption unless effective design methods are employed. High thermal comfort and low energy usage are often challenging to achieve at the same time. The potential for energy savings through strict control of indoor temperatures strengthens the case for examining the applicability of the universal comfort temperatures recommended by international comfort standards. The purpose of this paper is to evaluate energy conservation measures that support thermal environment conditions and have contributed to achieving architectural design features. The use of a systematic investigation of factors for energy conservation through a literature review revealed design features that have influenced the development of a comfortable environment; daylighting, acoustics, natural ventilation, and thermal control have all been identified as environmental factors in the implementation of architectural features in atriums. The outcome would aid in optimising the controlled environment during the original design stage, as well as providing useful feedback to assist architects and designers in determining the most energy-efficient atrium building type.